A CARE-compliant article: Biomechanics of treating early-stage femoral-head osteonecrosis by using a β-tricalcium phosphate bioceramic rod system. Issue 25 (June 2018) - Li, Bo; Hu, RuYin; Sun, Li; Luo, Rui; Zhao, JinMin; Tian, XiaoBin
Abstract : Abstract: The effect of implanting a β-TCP bioceramic rod system (BRS) can be observed with using the 3-dimensional (3D) finite-element method on the biomechanics of early-stage osteonecrosis of the femoral head (ONFH), to provide a theoretical basis for the biomechanics of applying the β-TCP BRS in the treatment of ONFH. A healthy 172 cm tall male adult volunteer (age: 40 years, weight: 70 kg, and femoral diameter: 50 mm) was selected for this study. The volunteer had no history of diseases in the hip, lower back, and lower limbs. He also had no history of trauma and surgery and had no lesions in the femoral head. A finite-element model of the normal proximal femur was constructed, and on this basis, 4 ONFH finite-element models were constructed, which had 15% and 30% necrotic areas in the superolateral area and 2 and 4 mm collapse in the weight-bearing area of the femoral head, respectively. This process was followed by simulated implantation of the β-TCP BRS in the finite-element models of the femoral head. Changes in the stress and displacement of the femoral head were observed before and after treatment with the β-TCP BRS, and the risk of femoral-head collapse was assessed. Under an applied walking load, the stress concentration on the femoral head was alleviated after treatment. Moreover, the stress and collapse values of the weight-bearing area decreased compared with those before treatment, and the differences were statistically significant ( P  < .05); the risk of collapse was also lower than that before treatment. As the area of the necrosis increased, the collapse value also increased, and the risk of collapse increased. More severe preoperative collapse implied that a greater risk of postoperative recollapse exists. This case report was written for 4 purposes: Implantation of the β-TCP BRS could effectively improve the internal mechanical properties of ONFH, enhance the support capacity of bones in the weight-bearing area in ONFH, reduce the compressive stress on the necrotic bone, and lower the risk of collapse in ONFH.